Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5505/tjtes.2016.77178
|View full text |Cite
|
Sign up to set email alerts
|

Complicated colorectal cancer in nonagenarian patients: is it better not to perform anastomosis in emergency?

Abstract: BACKGROUND: Colorectal cancer (CRC) is predominantly a disease of elderly people. Cancer in nonagenarian patients presents an ethical dilemma for surgeons and oncologists, and management of this group of patients in emergency for complicated CRC is debated. Presently described is retrospective study reporting experience of 6 departments of emergency surgery with management of nonagenarian patients sent to emergency surgery for CRC complications. METHODS: Data concerning patients aged over 90 years hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This finding is in line with those of De Simone et al. [ 19 ]. In a retrospective study, the authors found that patients with a more disadvantageous general condition (measured semiquantitatively by “American Society of Anesthesiologists” score) and acute symptoms benefit from a shorter operating time due to ostomy creation and avoidance of the more complication-prone anastomosis placement.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in line with those of De Simone et al. [ 19 ]. In a retrospective study, the authors found that patients with a more disadvantageous general condition (measured semiquantitatively by “American Society of Anesthesiologists” score) and acute symptoms benefit from a shorter operating time due to ostomy creation and avoidance of the more complication-prone anastomosis placement.…”
Section: Discussionsupporting
confidence: 94%
“…However, in the last decades CRC has been growingly increased in very old age subjects who are characterized by clinical conditions such as multimorbidity, cognitive impairment, malnutrition and frailty. Similarly, in the present case of a vulnerable centenarian patient with a cancer related obstruction of the right colon, the presence of hemodynamic instability, anemia, hypoalbuminemia and high inflammation had discouraged this recommended surgical approach because for the higher risk of anastomotic leakage, one of the most severe complications after colorectal surgery due to its associated higher morbidity and mortality [20].…”
Section: Discussionmentioning
confidence: 86%
“…Anastomosis after emergency surgeries shows a higher rate of anastomic leakage than elective surgery [8] . Decompressive stoma during emergency surgery is a bridge to elective surgery and also decreases morbidity and mortality in patients with high risk of anastomotic leakage [9] . For all these reasons, surgeons are not prejudiced about stoma opening in emergency operations.…”
Section: Discussionmentioning
confidence: 99%